Case report: Exploration of abrocitinib in the treatment of refractory chronic spontaneous urticaria: a case series - Du, Na; Wang, Dan; Yang, Jingyi; Zhang, Yiwen; Lyu, Xinyan; Min, Wei; Zhao, Sicheng (Frontiers in Immunology, 2024)
In clinical practice, some cases of chronic spontaneous urticaria (CSU) remain difficult to treat, with up to 40% of patients showing no response to even high (4-fold) daily doses of antihistamines. Approximately 30% of CSU patients fail to achieve complete control and relief through treatment with omalizumab and may require alternative therapies. Abrocitinib is a small-molecule oral JAK1 inhibitor that suppresses intracellular signaling of multiple key cytokines involved in inflammation cascades, and has shown beneficial effects in patients with mast cell activation disorders. We conducted a retrospective analysis of the diagnosis and treatment records of adult patients with refractory CSU who were treated with abrocitinib after inadequate response to omalizumab (defined as no response to 300 mg/4 weeks of omalizumab treatment for 6 months, followed by adjustment to 300 mg/2 weeks for a further 3 months without controlling symptoms). We also collected data on relevant treatment modalities, clinical outcomes, and adverse events. Among these patients, various treatment modalities failed to adequately control symptoms, but switching to abrocitinib significantly improved clinical outcomes. Therefore, abrocitinib may represent a new treatment option for patients with refractory CSU.